Structural and Biophysical Mechanisms of Class C G Protein-Coupled Receptor Function. Issue 12 (December 2020) - Ellaithy, Amr; Gonzalez-Maeso, Javier; Logothetis, Diomedes A.; Levitz, Joshua
Abstract : Groundbreaking structural and spectroscopic studies of class A G protein-coupled receptors (GPCRs), such as rhodopsin and the β2 adrenergic receptor, have provided a picture of how structural rearrangements between transmembrane helices control ligand binding, receptor activation, and effector coupling. However, the activation mechanism of other GPCR classes remains more elusive, in large part due to complexity in their domain assembly and quaternary structure. In this review, we focus on the class C GPCRs, which include metabotropic glutamate receptors (mGluRs) and gamma-aminobutyric acid B (GABAB ) receptors (GABAB Rs) most prominently. We discuss the unique biophysical questions raised by the presence of large extracellular ligand-binding domains (LBDs) and constitutive homo/heterodimerization. Furthermore, we discuss how recent studies have begun to unravel how these fundamental class C GPCR features impact the processes of ligand binding, receptor activation, signal transduction, regulation by accessory proteins, and crosstalk with other GPCRs. Highlights: Class C G protein-coupled receptors (GPCRs) show a unique multidomain structure and dimeric assembly that allows a complex interplay between orthosteric ligand-binding domains (LBD)-targeting and allosteric transmembrane domain (TMD)-targeting ligands Rapid inter-LBD rearrangement on the millisecond timescale drives receptor activation, in part, by repositioning the TMDs relative to each other. Class C GPCRs interact with a plethora of accessory proteins, including intracellular scaffold proteins, secreted proteins, intersynaptic scaffolds, and class A GPCRs, which tune their biophysical and signaling properties.